2012
DOI: 10.1111/j.1540-8183.2012.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness Analysis of Anticoagulant Strategies in a Large Observational Database of Percutaneous Coronary Interventions

Abstract: Bivalirudin use was associated with both improved clinical outcomes and decreased hospital costs in this large "real-world" database. To our knowledge, this study is the first to demonstrate the ideal comparative effectiveness end-point of both improved clinical outcomes with decreased costs in PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
4
0
2
Order By: Relevance
“…[4][5][6] Large database observational studies have confirmed these findings in real-world practice and have also demonstrated lower in-hospital mortality with bivalirudin compared with heparin-based regimens. 7,16,17 PVI has been recently documented to improve health-related quality of life 3 ; however, the optimal adjunctive anticoagulant strategy has not been defined. Because of the procedural similarities between PCI and PVI, many operators have adopted the use of UFH and bivalirudin as procedural anticoagulation based on their performance in the PCI arena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Large database observational studies have confirmed these findings in real-world practice and have also demonstrated lower in-hospital mortality with bivalirudin compared with heparin-based regimens. 7,16,17 PVI has been recently documented to improve health-related quality of life 3 ; however, the optimal adjunctive anticoagulant strategy has not been defined. Because of the procedural similarities between PCI and PVI, many operators have adopted the use of UFH and bivalirudin as procedural anticoagulation based on their performance in the PCI arena.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 More than 5 million inpatient discharges and 35 million outpatient visits are recorded annually. The database records standard data elements available in most hospital discharge files, such as demographic data, diagnoses, and procedures performed (International Classification of Diseases Ninth Revision, clinical modification [ICD-9-CM] diagnosis and procedural codes), and discharge destination.…”
Section: Kimmelstiel Et Al Bivalirudin In Peripheral Vascular Intervementioning
confidence: 99%
“…Those deficiencies aside, this real‐world analysis is important given the large number of patients reported on. Pinto et al's findings reiterate prior analyses within the same database albeit in a more specific patient population .…”
mentioning
confidence: 71%
“…Na podstawie analizy danych uzyskanych z rejestru PREMIER, obejmującym 458 448 pacjentów hospitalizowanych w Stanach Zjednoczonych i poddawanych PCI, wykazano, że podanie biwalirudyny w porównaniu z UFH + inhibitor GP IIb/IIIa w istotny statystycznie sposób redukuje ryzyko wystąpienia poważnych krwawień prowadzących do konieczności przetoczenia krwi (1,6% vs. 2,6%, p < 0,0001), a także poważnych krwawień bez względu na konieczność wykonania transfuzji (7,3% vs. 9,4%; p < 0,0001) oraz transfuzji bez względu na związek z krwawieniem (5,7% vs. 6,8; p = 0,0006) [14]. Stwierdzono również, że stosowanie biwalirudyny w monoterapii znamiennie statystycznie zmniejsza ryzyko zgonu wewnątrzszpitalnego w porównaniu z zastosowaniem UFH + inhibitor GP IIb/IIIa.…”
Section: Wyniki Badań Klinicznych Z Udziałem Biwalirudyny U Chorych Z...unclassified